2010
DOI: 10.1175/2009mwr3068.1
|View full text |Cite
|
Sign up to set email alerts
|

Morning Precipitation Peak over the Strait of Malacca under a Calm Condition

Abstract: This paper describes the formation mechanism of morning maximum in the diurnal cycle of precipitation, at the Strait of Malacca under a calm condition, with a nonhydrostatic mesoscale numerical model and shipbased observational data. The morning precipitation peak at the strait is induced by the convergence of two cold outflows that have been produced by the precipitation systems in the previous evening over Sumatra and the Malay Peninsula. The outflows converge at the Strait of Malacca around midnight; a new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 16 publications
3
41
0
Order By: Relevance
“…Some previous studies suggest that cold pool dynamics are important to the redevelopment of rainfall systems over the ocean [Sakurai et al, 2009[Sakurai et al, , 2011Fujita et al, 2010]. Cold pools, however, are associated with intense downdrafts produced in the convective core [Feng et al, 2015].…”
Section: Comparison Between Diurnal Rainfall Propagation and Zonal Wimentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous studies suggest that cold pool dynamics are important to the redevelopment of rainfall systems over the ocean [Sakurai et al, 2009[Sakurai et al, , 2011Fujita et al, 2010]. Cold pools, however, are associated with intense downdrafts produced in the convective core [Feng et al, 2015].…”
Section: Comparison Between Diurnal Rainfall Propagation and Zonal Wimentioning
confidence: 99%
“…The relevant processes reported in previous studies include land breeze convergence [Houze et al, 1981], advection by background wind [Mori et al, 2004;Sakurai et al, 2009Sakurai et al, , 2011, self-replication of convective cells [Sakurai et al, 2009[Sakurai et al, , 2011, convergence of cold outflows produced by rainfall systems [Fujita et al, 2010], and gravity waves triggered by daytime heating of the mixed layer on land [Mapes et al, 2003] or convection on land [Love et al, 2011]. effects of seasonality on the diurnal propagation of precipitation systems.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the strait of Malacca exhibits the second highest flash density. Fujita et al (2010) suggested that gravity currents generated by precipitation over the eastern and western coastal area of Sumatra and Malay Peninsula can converge and trigger convection over the strait. Teo et al (2011) proposed that the strait of Malacca can be seen as a wave cavity.…”
Section: Spatial Distributionmentioning
confidence: 99%
“…This deep convective transport can be attributed to a strong orographic effect which occurs as the wind is force-lifted over the slope on the West coast of Malaysia and its mountains deeper inland. As the morning precipitation maximum forms (Fujita et al, 2010) at 18 UTC, a higher concentration PM 10 plume rises to at least 200 hPa over the Strait of Malacca as shown in Fig. 8(b) confirming further the transport of biomass burning emissions to the upper troposphere in the region.…”
Section: Vertical Pm 10 Emissions Transport and Deep Convective Motionmentioning
confidence: 53%
“…Hence only the results obtained June along both cross-sections. Fujita et al (2010) described the mechanism by which a morning maximum in the diurnal precipitation was formed by the convergence of cold outflows from Sumatra and Peninsular Malaysia over the Strait. These outflows are generally produced by precipitation systems from the previous evening and converge over the Strait at around midnight.…”
Section: Vertical Pm 10 Emissions Transport and Deep Convective Motionmentioning
confidence: 99%